Stop and Go Nodes of Transformation and Transition - Hieslmair, Michael; Zinganel, Michael (Publication Serie of the Academy of Fine Arts Vienna, 2019)
"Stop and Go: Nodes of Transformation and Transition was a research project by architect and artist Michael Hieslmair and cultural historian Michael Zinganel from Vienna in collaboration with geographer Tarmo Pikner from Tallinn and historian and anthropologist Emiliya Karaboeva from Sofia. The project focused on the transformation of hubs and terminals as well as formal and informal nodes along the network of pan-European road transport corridors connecting the former East and West of Europe. The book presents several trans-disciplinary case studies in the geographical triangle between Vienna, Tallinn and Helsinki and the Bulgarian-Turkish border. Each contribution investigates how differently the networks and temporary habitats of highly mobile actors along these road corridors - both in the posturban intermediate zones and in the city centers - have undergone and continue to undergo significant changes before and after the fall of the Iron Curtain, the enlargement of the EU, and the re-expansion of transport infrastructure."